O teste ergométrico em indivíduos com obesidade mórbida - Fornitano, Luis Domingos (2008)
Obesity is an independent risk factor for cardiovascular disease, especially in its morbid form. Bariatric surgery is an effective therapeutic option for sustained weight loss. However, there is no consensus in these cases regarding the performance of functional tests for preoperative evaluations. Objective: The aim of the present study was to analyze clinical, electrocardiographic and hemodynamic response variables using a conventional exercise test on individuals with morbid obesity in comparison to overweight individuals. Materials and Method: Six hundred seventeen cases were included. Group I had 290 patients with morbid obesity and Group II had 327 overweight patients. All were submitted to a conventional treadmill exercise test. Classic positivity criteria were used. Results: Both groups tolerated the test well. There was no statistically significant difference in terms of positivity of the test [ST segment abnormality or angor (p=0.3863) or ST segment abnormality alone (p=0.1000)]. The significantly higher values in the obese individuals were basal heart rate (HR), basal sistolic arterial pressure (SAP), maximum SAP, basal diastolic arterial pressure (DAP), maximum DAP, chronotropic incompetence (p<0.0001) and maximum double product (p<0.0421). The significantly lower values in the obese individuals were exercise time, maximum HR and METs values (p<0.0001). Conclusions: Hemodynamic parameters were significantly different between the two groups. However, there were no differences in terms of ST segment abnormalities or effort-induced angina. The very low functional capacity and complex arrhythmia found in some obese individuals draws attention to the need for complementary investigation with the aim of diminishing the risk of postoperative heart complications.